Resurrection of Wheat Cultivar PBW343 Using Marker-Assisted Gene Pyramiding for Rust Resistance - Sharma, Achla; Srivastava, Puja; Mavi, G. S.; Kaur, Satinder; Kaur, Jaspal; Bala, Ritu; Singh, Tarvinder Pal; Sohu, V. S.; Chhuneja, Parveen; Bains, Navtej S.; Singh, G. P. (Frontiers in Plant Science, 2021)
Wheat variety PBW343, released in India in 1995 became the most widely grown cultivar in the country by year 2000 owing to its wider adaptability and yield potential. It initially succumbed to leaf rust and resistance genes Lr24 and Lr28 were transferred to PBW343. After an unbroken reign of about ten years, the virulence against gene Yr27 made PBW343 susceptible to stripe rust. Owing to its with wider adaptability and yield potential, PBW343 became the prime target for marker assisted introgression of stripe rust resistance genes. The leaf rust resistant versions formed the base for pyramiding stripe rust resistance genes Yr5, Yr10, Yr15, Yr17 and Yr70, in different introgression programs. Advance breeding lines having different gene combinations, PBW665, PBW683, PBW698 and PBW703 were tested in national trials but could not be released as varieties. The genes from alien segments, Aegilops ventricosa (Lr37/Yr17/Sr38) and Aegilops umbellulata (Lr76/Yr70) were later pyramided in PBW343. Modified marker assisted backcross breeding was performed and 81.57% of the genetic background was recovered in one of the selected derivative lines, PBW723. This line was evaluated in the national coordinated trials and was released for cultivation under timely sown irrigated conditions in North Western Plain Zone of India. PBW723 yields at an average 58.0 qtl/ha in Punjab with high potential yields. The genes incorporated are susceptible to stripe rust individually, but together confer resistance in farmer’s fields. Three years post release, PBW723 occupies approximately 8-9% cultivated area in Punjab state. Regular inflow of diverse resistant genes, their rapid mobilization to most productive backgrounds and keeping a close eye on pathogen evolution is essential to protect the overall progress for productivity and resistance in wheat breeding, thus helping breeders to keep pace with pathogen evolution.